More than "Good Job!": The Critical Role of Teacher Feedback in Classroom Discourse and Language Development. (20th May 2022) - Wasik, Barbara A.; Farrow, JeanMarie; Hindman, Annemarie H.
Abstract: Conversations between an adult and a child are effective ways to promote language and vocabulary development in young children. Considerable attention has been paid to teachers asking open‐ended questions to promote conversations. However, the feedback that follows the question is also an important part of promoting back‐and‐forth dialogue, and less attention has been paid to this aspect of an exchange. Teachers' feedback uniquely encourages conversations beyond one back‐and‐forth turn, essential for promoting rich adult–child language interactions. This paper discusses the role of teacher feedback in extending conversations that encourage children to use language in meaningful ways. We review the research findings on teacher feedback and offer evidenced‐based, practical suggestions on providing feedback, meant to support teachers and children as they engage in conversations. Asking open‐ended questions is one part of meaningful conversations; feedback extends the conversation and supports children's language development.